Employee Performance Analysis at CV. Sinar Jaya Gypsum Kaliwungu - Rizkia, Rizkia Mubarika; Sumastuti, Efriyani; Setyorini, Noni (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to determine the effect of employee performance on CV Sinar Jaya Gypsum Kaliwungu The object of this research is the employees of CV Sinar Jaya Gypsum with a sample size of 120 employees using a sampling technique that is saturated sampling. This research data was obtained primary through the distribution of questionnaires (angeket). Data analysis in this study used multiple linear regression analysis techniques with the Statistical Package for Social Sciences (SPSS) program. The results of the analysis and discussion show that partially the work environment variable has no significant effect on employee performance by 13.8%, work discipline has no significant effect on employee performance by 5.5%, work motivation has a significant effect on employee performance by 32.2%, k3 has a significant effect on employee performance by 48.8% and incentives have a significant effect on employee performance by 54.1% Simultaneously the work environment variables, work discipline, work motivation, k3 and incentives have a significant effect on employee performance by 63.1% and 36.9% are influenced by other variables outside the model specified in the study.